Subgroup specific transcriptional regulation of salmonid non-classical MHC class I L lineage genes following viral challenges and interferon stimulations - Imam, Maryam; Kianian, Atefeh; Bhat, Shripathi; Fure Lukes, Viktoria Erika; Greiner-Tollersrud, Linn; Edholm, Eva-Stina (Frontiers in Immunology, 2024)
Non-classical MHC class I genes which, compared to classical MHC class I, are typically less polymorphic and have more restricted expression patterns are attracting interest because of their potential to regulate immune responses to various pathogens. In salmonids, among the numerous non-classical MHC class I genes identified to date, L lineage genes, including Sasa-LIA and Sasa-LGA1, are differentially induced in response to microbial challenges. In the present study, we show that while transcription of both Sasa-LIA and Sasa-LGA1 are induced in response to SAV3 infection the transcriptional induction patterns are distinct for each gene. While elevated Sasa-LGA1 expression is maintained long-term following in vivo SAV3 infection Sasa-LIA expression is transient, returning to near baseline weeks prior to viral clearance. Furthermore, by contrasting L lineage transcriptional induction potential of SAV3 with that of IPNV we show that Sasa-LIA and Sasa-LGA1 transcriptional induction is tightly interconnected with select type I and type II interferon induction. Both type I and type II interferon stimulation, to varying degrees, induce Sasa-LIA and Sasa-LGA1 expression. Compared to IFNa1 and IFNc, IFN-gamma was a more effective inducer of both Sasa-LIA and Sasa-LGA1 while IFNb showed no activity. Furthermore, IFNa was a more potent inducer of Sasa-LIA compared to IFNc. The involvement of type I IFN and IFN gamma in regulation of Sasa-LIA and Sasa-LGA1 expression was further substantiated by analysis of their respective promoter regions which indicate that ISRE and GAS like elements most likely cooperatively regulate Sasa-LIA expression while IFN gamma induced expression of Sasa-LGA1 is critically dependent on a single, proximally located ISRE element. Together, these findings imply that Sasa-LIA and Sasa-LGA1 play important but likely functionally distinct roles in the anti-viral response of salmonids and that these two molecules may serve as immune regulators promoting more effective antiviral states.